The influence of the land-sea breeze on coastal upwelling systems - Fearon, Giles (Department of Oceanography, 2022)
The land-sea breeze is resonant with the inertial response of the ocean at the critical latitude of 30° N/S, however its role in the physical and biogeochemical functioning of eastern boundary upwelling systems (EBUS) is often over-looked. Here, we present a series of 1D, 2D, and 3D numerical experiments which elucidate the drivers of diurnal-inertial variability and vertical mixing in EBUS due to land-sea breeze forcing near the critical latitude. The amplitude of the diurnal anticyclonic rotary component of the wind stress (τ ac0 ) is shown to be a good predictor of the locally forced response. The water depth plays an important role, where for shallow water depths (<∼100 m) surface oscillations are dampened and shear-driven mixing at the thermocline is reduced. Convergence/ divergence of the forced surface oscillations drive evanescent internal waves which elevate local vertical mixing above that from the forced response alone. The internal wave response is dampened by a gradually sloping bottom topography. St Helena Bay (∼32.5° S), in the southern Benguela upwelling system, possesses a combination of physical characteristics which favour an enhanced response to the land-sea breeze, namely a near-critical latitude, a local enhancement of τ ac0 , and a tendency for the development of a shallow stratified surface layer. Here, land-sea breeze forcing contributes to large diurnal variability in sea surface temperatures (SST's). During relaxation events, mean SST's are notably reduced due to land-sea breeze-driven vertical mixing. During upwelling events, the land-sea breeze drives a net warming of inner shelf waters primarily due to enhanced retention of the deepened surface mixed layer. The deepened thermocline impacts geostrophically-driven alongshore currents within St Helena Bay, which are strengthened (weakened) during upwelling (relaxation) events. It appears likely that the land-sea breeze plays an important role in the productivity of the system.